Math/Science Program. (Education Digest, 1984)
The article presents information related to the recent educational developments in the U.S. The Connecticut State Department of Education, Wesleyan University, the Connecticut Academy of Science and Engineering, General Electric Foundation, and several Connecticut corporations are jointly supporting a fellowship program designed to develop a cadre of talented high school "fellows" who can work with other teachers to improve math and science education in their school districts. A pilot program with 12 teachers will precede the opening of the full program this summer.